2013
DOI: 10.1017/erm.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mediators in the pathogenesis of periodontitis

Abstract: Periodontitis is a chronic inflammatory condition of the periodontium involving interactions between bacterial products, numerous cell populations and inflammatory mediators. It is generally accepted that periodontitis is initiated by complex and diverse microbial biofilms which form on the teeth, i.e. dental plaque. Substances released from this biofilm such as lipopolysaccharides, antigens and other virulence factors, gain access to the gingival tissue and initiate an inflammatory and immune response, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
351
1
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(376 citation statements)
references
References 221 publications
(246 reference statements)
6
351
1
18
Order By: Relevance
“…As a result, inflammatory mediators, including cytokines, chemokines and proteolytic enzymes, are produced and contribute to tissue degradation and bone resorption. Neutrophils are the first cells to arrive at the inflammatory inflitrate and predominate within the junctional epithelium and gingival crevice [18] . Previous studies from our group have shown that neutrophils from periodontitis patients are hyper-reactive and contribute to tissue destruction [3,19,20] .…”
Section: Periodontal Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…As a result, inflammatory mediators, including cytokines, chemokines and proteolytic enzymes, are produced and contribute to tissue degradation and bone resorption. Neutrophils are the first cells to arrive at the inflammatory inflitrate and predominate within the junctional epithelium and gingival crevice [18] . Previous studies from our group have shown that neutrophils from periodontitis patients are hyper-reactive and contribute to tissue destruction [3,19,20] .…”
Section: Periodontal Diseasementioning
confidence: 99%
“…When the resolution of inflammation is not achieved, antigen-presenting cells are activated by bacterial pro-ducts and interact with naïve T helper cells (Th0), driving their differentiation into several subsets, such as Th1, Th2, Th17, and Treg. These subsets are characterized according to the cytokines they produce [18] . For a long time, periodontitis lesions were conceptually defined based on a Th1/Th2 paradigm, with inconclusive studies pointing to both Th1 and Th2 responses as characterizing disease progression [23] .…”
Section: Periodontal Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…As the other chronic inflammatory diseases inflammatory cytokines are considered to play an important role in the initiation, progression and the host modulation of periodontal disease [12,13] Current knowledge supports that the immunoregulatory properties of T cell derived cytokines can improve or attenuate the progression of periodontal disease [14]. There is evidence that failure to resolve inflammatory periodontal disease may be the result of an imbalance in T helper (Th) 1, Th2 and Th17 response and pro-and anti-inflammatory cytokines [14][15][16][17]. Therefore, in this mini-review, the Th cell subsets and their cytokines which are involved in the host inflammatory response and the destruction of periodontal tissues are summarized.…”
Section: Introductionmentioning
confidence: 99%